Primary leiomyosarcoma of kidney: A rare case report - Pooja Srivastava; Rajni Prasad; Geetika Khanna (Wolters Kluwer Medknow Publications, 2015)
Primary leiomyosarcoma of kidney is extremely rare tumour accounting for 0.12% of renal tumours. Radiological investigations are not able to differentiate between leiomyosarcoma and sarcomatoid renal cell carcinoma. Histopathological examination along with aid of immunohistochemistry is required to make a definitive diagnosis. We present a rare case of primary renal leiomyosarcoma occurring in a 50 years old female.